1997
DOI: 10.1289/ehp.971051360
|View full text |Cite
|
Sign up to set email alerts
|

Health advisories for consumers of Great Lakes sport fish: is the message being received?

Abstract: Nationwide, 45 states issue health advisories for sport fish consumers. Chemical contaminants in some Great Lakes (GL) sport fish include compounds suspected of causing adverse reproductive and developmental effects. Although advisories to reduce consumption of contaminated fish, especially by women, have been issued by GL states (i.e., Illinois, Indiana, Michigan, Minnesota, New York, Ohio, Pennsylvania, and Wisconsin) since the mid-1970s, little is known about advisory awareness and GL sport fish consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 17 publications
(12 reference statements)
1
43
0
Order By: Relevance
“…This resemblance in PCB body burden between the Mohawk and the Obijwe and Menominee peoples reflects similarity in their rates of local fish consumption, which currently averaged 21.2 meals per year for the Mohawk men and ranged from 12 to 34 meals per year for the Obijwe and Menominee. Consumption rates for both native groups are greater than the median of 6.5 sport fish meals per year reported for the general population of the Great Lakes states (Tilden et al, 1997). In contrast, much higher serum PCB levels have been observed among the Inuit people, who are much more dependent on local fish and other PCB-contaminated marine food sources than are the Mohawks (Ayotte et al, 1997).…”
Section: Discussionmentioning
confidence: 77%
“…This resemblance in PCB body burden between the Mohawk and the Obijwe and Menominee peoples reflects similarity in their rates of local fish consumption, which currently averaged 21.2 meals per year for the Mohawk men and ranged from 12 to 34 meals per year for the Obijwe and Menominee. Consumption rates for both native groups are greater than the median of 6.5 sport fish meals per year reported for the general population of the Great Lakes states (Tilden et al, 1997). In contrast, much higher serum PCB levels have been observed among the Inuit people, who are much more dependent on local fish and other PCB-contaminated marine food sources than are the Mohawks (Ayotte et al, 1997).…”
Section: Discussionmentioning
confidence: 77%
“…While aware of these uncertainties, public health agencies in the Great Lakes region have issued public warnings about the potential risks related to eating Great Lakes fish. Unfortunately, however, studies indicate that fish consumption advisories do not reach many anglers and their families, and when advisories are received, they are often discounted or ignored (Burger, 2000;Tilden et al, 1997). Moreover, little to nothing is known about awareness, knowledge, and uncertainties among the general public (including non-anglers) about the risks from eating Great Lakes fish.…”
Section: The Risk Issue: Consumption Of Contaminated Great Lakes Fishmentioning
confidence: 99%
“…In other studies, respondents reported incomplete or inaccurate information about the contamination of the fish and/or lack of trust in the organization issuing the advisory (Burger 1998;May and Burger 1996;Steenport et al 2000;Tilden et al 1997). Furthermore, risk perceptions are usually optimistically biased; individuals believe their own risk from a voluntary activity is less than someone else's risk (Weinstein 1989).…”
Section: Discussionmentioning
confidence: 99%